2014
DOI: 10.1371/journal.pone.0104797
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Dopamine Intrinsic Direct Role in the Regulation of the Ovary Reproductive Function: In Vitro Study on Rabbit Corpora Lutea

Abstract: Dopamine (DA) receptor (DR) type 1 (D1R) has been found to be expressed in luteal cells of various species, but the intrinsic role of the DA/DRs system on corpora lutea (CL) function is still unclear. Experiments were devised to characterize the expression of DR types and the presence of DA, as well as the in vitro effects of DA on hormone productions by CL in pseudopregnant rabbits. Immunoreactivity and gene expression for D1R decreased while that for D3R increased in luteal and blood vessel cells from early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Following antioxidant administration, the murine ovarian transcriptome reflected an environment with enhanced cell survival and β-adrenergic signaling, decreased apoptotic signaling proinflammatory pathways, and altered antioxidant signaling compared to control aged mice. Upregulated β-adrenergic signaling may contribute to improved ovarian function through changes in follicular development and hormone secretion [37][38][39], particularly since ovarian sympathetic nerve activity may decline with ovarian aging [40]. The anti-inflammatory effects of antioxidant treatment are consistent with previous reports [41].…”
Section: Discussionsupporting
confidence: 81%
“…Following antioxidant administration, the murine ovarian transcriptome reflected an environment with enhanced cell survival and β-adrenergic signaling, decreased apoptotic signaling proinflammatory pathways, and altered antioxidant signaling compared to control aged mice. Upregulated β-adrenergic signaling may contribute to improved ovarian function through changes in follicular development and hormone secretion [37][38][39], particularly since ovarian sympathetic nerve activity may decline with ovarian aging [40]. The anti-inflammatory effects of antioxidant treatment are consistent with previous reports [41].…”
Section: Discussionsupporting
confidence: 81%
“…The slope of these graphs was used to determine the reaction efficiency. Sample mRNA quantification was evaluated using iCycler system software, while mRNA gene expression was quantified using the 2 –ΔΔCt method [22,23]. The melting curve analysis was carried out, immediately after the PCR end cycle, in order to determine the specificity of each primer set.…”
Section: Methodsmentioning
confidence: 99%
“…It was reported that DA/DR system exerts a dual modulatory function in the lifespan of corpora lutea (the DA/D1R as luteotropic and the DA/D3R as luteolytic). 70…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that DA/DR system exerts a dual modulatory function in the lifespan of corpora lutea (the DA/D1R as luteotropic and the DA/ D3R as luteolytic). 70 Among the investigated molecules, aristola-1(10),8-dien, b-humulene, bicyclogermacrene, a-bisabolol oxide A, a-bisabolone oxide, coumarin-7-methoxy (herniarin, umbelliferone), b-eudesmol, ficusin, methyl jasmonate, nerolidol, p-cymen-8-ol, pinocarvone, spathulenol, thujone, (þ)-spathulenol, 7-epi-b-eudesmol, cis-a-bergamotene, trans-a-bergamotene, and (E)-methyl jasmonate (Figure 1) had a reasonable interaction with the dopamine receptors. The binding energy for the named ligands ranged from 88.60% to 100% of the cocrystallized ligand of the dopamine receptor.…”
Section: Dopamine Receptorsmentioning
confidence: 99%